Ex Officio Rights of Judges in Divorce of Inter-Country Couples (Decision No. 725/Pdt.G/2025/PA.Btl) - Halimah Siti Rahmawati (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the application of ex officio rights of judges in divorce cases between couples of different nationalities as reflected in Decision Number 725/Pdt.G/2025/PA.Btl. The focus of the study is directed at how judges use ex officio authority to protect the rights of wives and children, and uphold the principle of justice in the context of differences in nationality. The method used is normative legal research. The results of the study indicate that judges have ex officio authority to determine iddah maintenance, madhiyah maintenance, mut'ah, and hadhanah rights in accordance with the principles of propriety and legal protection. The application of this authority in Decision Number 725/Pdt.G/2025/PA.Btl is based on justice, appropriateness and propriety after the judge considers the capabilities of the counter-defendant and the basic needs in the area of ​​the counter-plaintiff. Therefore, it can be concluded that the application of ex officio rights accommodates the needs of vulnerable groups, especially women and children in divorce based on substantive justice. Decision Number 725/Pdt.G/2025/PA.Btl reflects that this right also applies in international civil law, so it needs to be encouraged with a concrete mechanism to be more effective.